Quilted projects with wool and wool felt : easy technique with full-size templates - Pellman, Rachel T. (Rachel Thomas); Oberholtzer, Beth. (East Petersburg : Design Originals, 2014)
"Even beginners can get delightful results with wool and wool felt applique;. The texture and color saturation of 100% wool fabric add warmth and glow to any project. This friendly book reveals everything you need to know to begin a memorable quilting adventure. Ideal for beginners, it teaches all the basics of applique; and quilt, including tools, materials, and stitching, plus how cut, fold, and sew binding to finish edges. Four simple and adorable projects are provided for making chicken hot pads, an owl pillow pair, a meadow wall quilt, and a nature wall quilt. Each easy-to-sew project is small and comes together quickly. Supporting layout diagrams and templates are provided at actual size, and can be used directly from the book with no photocopying or resizing. Cutting templates are printed on one side of the page only, so you can snip them out with no worries about ruining the other side. Step-by-step instructions are provided for each project, along with a matching layout diagram for assembling your cut applique; pieces"--
"Presents basic instructions and projects for quilting with wool and wool felt, including information on tools, fabrics, piecing, applique and binding. Features five projects with layout diagrams and cutting templates"--
Includes index.
Keywords: Quilting -- Patterns; Appliqué -- Patterns; Wool fabrics; CRAFTS & HOBBIES / Needlework / General